Facilitators and barriers for healthcare workers' adherence to the national nutritional guidelines for people living with HIV in Dar-es-Salaam: A mixed-method study. - Felistar Mwakasungura; Rebecca Mkumbwa; Bruno Sunguya (PLOS Global Public Health)
The dual burden of HIV and malnutrition is a significant public health challenge in high burden Sub-Saharan African countries. Tanzania is no exception. Care and treatment of HIV has been strengthened in these countries, however integration with nutrition care and support remains poor. This study evaluated adherence to nutritional guidelines for people living with HIV (PLHIV) in Dar es Salaam Tanzania and identified its influencing factors. A mixed method study was conducted among PLHIV, health facility administrators, and healthcare providers from April 29 to May 27, 2024. Data were collected through observation checklists, structured questionnaires, and in-depth interviews. Statistical and qualitative analyses were performed to assess adherence and determinants. Among 478 participants who received care, only 19.5% were managed while adhering to the national nutritional guidelines. Universally, anthropometric assessments were taken, however, only 1% received micronutrient supplements. Higher education (AOR = 5.08, p = 0.019) and attendance at referral hospitals (AOR = 8.23, p = 0.032) positively influenced adherence. Conversely, nurse attendance (AOR = 0.34, p = 0.038), adequate staffing (AOR = 0.31, p = 0.010), and urban residence (AOR = 0.47, p = 0.009) negatively influenced adherence. Key facilitators included consistent training and supportive leadership while financial constraints and high staff turnover remained important barriers. There is a significant gap in adherence to nutritional guidelines among PLHIV in Dar es Salaam, Tanzania. This highlights the need for improved resource distribution, staff training, and clients education in Tanzania and countries with similar contexts.